The personal is global political: The antifeminist backlash in the United Nations - Jelena Cupać; Irem Ebetürk (British Journal of Politics and International Relations, 2020)
Antifeminist mobilisation is growing in the United Nations. It is led by a coalition of certain post-Soviet, Catholic, and Islamic states; the United States; the Vatican; conservative nongovernmental organisations, occasionally joined by the Organisation for Islamic Cooperation, the League of Arab States, the UN Africa Group, and the G77. Uniting them is the aim of restoring the `natural family' and opposing `gender ideology'. The group has become increasingly strategic, and its impact can already be seen in a number of UN fora, including the Security Council. By surveying feminist notions of backlash and comparing them to Alter and Zürn's definition of `backlash politics', the article gauges whether the group's activities can be characterised as such politics. The conclusion is that they can, suggesting that we are looking at a group with the potential to alter not only the global course of women's rights but also how politics is done within the UN.
Keywords: 300; antifeminism; backlash; family; gender; transnational movements; United Nations; women's rights